The development of task sharing policy and guidelines in Kenya - Rosemary Kinuthia; Andre Verani; Jessica Gross; Rose Kiriinya; Kenneth Hepburn; Jackson Kioko; Agnes Langat; Abraham Katana; Agnes Waudo; Martha Rogers (BMC, 2022)
Abstract Background The global critical shortage of health workers prevents expansion of healthcare services and universal health coverage. Like most countries in sub-Saharan Africa, Kenya's healthcare workforce density of 13.8 health workers per 10,000 population falls below the World Health Organization (WHO) recommendation of at least 44.5 doctors, nurses, and midwives per 10,000 population. In response to the health worker shortage, the WHO recommends task sharing, a strategy that can increase access to quality health services. To improve the utilization of human and financial health resources in Kenya for HIV and other essential health services, the Kenya Ministry of Health (MOH) in collaboration with various institutions developed national task sharing policy and guidelines (TSP). To advance task sharing, this article describes the process of developing, adopting, and implementing the Kenya TSP. Case presentation The development and approval of Kenya's TSP occurred from February 2015 to May 2017. The U.S. Centers for Disease Control and Prevention (CDC) allocated funding to Emory University through the United States President's Emergency Plan for AIDS Relief (PEPFAR) Advancing Children's Treatment initiative. After obtaining support from leadership in Kenya's MOH and health professional institutions, the TSP team conducted a desk review of policies, guidelines, scopes of practice, task analyses, grey literature, and peer-reviewed research. Subsequently, a Policy Advisory Committee was established to guide the process and worked collaboratively to form technical working groups that arrived at consensus and drafted the policy. The collaborative, multidisciplinary process led to the identification of gaps in service delivery resulting from health workforce shortages. This facilitated the development of the Kenya TSP, which provides a general orientation of task sharing in Kenya. The guidelines list priority tasks for sharing by various cadres as informed by evidence, such as HIV testing and counseling tasks. The TSP documents were disseminated to all county healthcare facilities in Kenya, yet implementation was stopped by order of the judiciary in 2019 after a legal challenge from an association of medical laboratorians. Conclusions Task sharing may increase access to healthcare services in resource-limited settings. To advance task sharing, TSP and clinical practice could be harmonized, and necessary adjustments made to other policies that regulate practice (e.g., scopes of practice). Revisions to pre-service training curricula could be conducted to ensure health professionals have the requisite competencies to perform shared tasks. Monitoring and evaluation can help ensure that task sharing is implemented appropriately to ensure quality outcomes.